If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + -3(-2) = 4 Multiply -3 * -2 Y + 6 = 4 Reorder the terms: 6 + Y = 4 Solving 6 + Y = 4 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + Y = 4 + -6 Combine like terms: 6 + -6 = 0 0 + Y = 4 + -6 Y = 4 + -6 Combine like terms: 4 + -6 = -2 Y = -2 Simplifying Y = -2
| 3.0+3.0x=3.2 | | 4-x=[2-3x] | | 7-.625x=-2 | | .75x=180 | | 4(0)+2y=6 | | 100=10(logI-logI[0]) | | ax+by+1=0 | | 4(-1)+2y=6 | | 100=.50x-(15+.05x) | | 0.50x-(15+.05x)=100 | | (5x+1)(5x+1)=9 | | 2=6(5-4w) | | F-1(2)=2x-6 | | 8x+12y=144 | | 3(7a-1)= | | (3x-2)+(2x+4)+(x+10)=0 | | 8-2c=9 | | 52=-2w*3L | | 7-9g+8+2g= | | 10(-10x-5)= | | 10p+9-11-p=-4p+-8-6p-3 | | 7+9g-8+2g= | | 3x-(9)=75+x | | 3x-2+2x+4+x+10=o | | -61=12a-1 | | 3x^2+3y^2=6 | | 53=5-2u | | 1-8k-9k-4= | | 29-4x=4 | | 2y+9fory=-6 | | 6f-7f-1=-5-5f | | 3a+a+25=225 |